Effects of Air Borne Particulate Matter on the Plants Grown in Different Areas of Dhaka Mega City, Bangladesh: An Air Pollution Tolerance Study. Issue 4 (2nd October 2021) - Binte Jashim, Zuairia; Akhtar Hossain, Shahid; Enayet Hossain, Mohammad; Islam, Md. Mominul; E-Gulshan, Jahan-; Nurul Huda, Muhammad
Abstract: Air Pollution Tolerance Index (APTI) was used to assess four plant species, namely Mangifera indica, Artocarpus heterophyllus, Psidium guajava and Sweitenia mahagoni for their response toward air pollution in Dhaka city. Leaf samples of the plant species were analyzed for their physicochemical and biochemical attributes, including relative water content, leaf extract pH, ascorbic acid content and chlorophyll content. APTI values of all the plant species were found to be sensitive with respect to air pollution. Our results indicate that the studied plant species are not suitable for mitigating air pollution and should not be considered for urban roadside plantation. Supplemental data for this article can be accessed at https://doi.org/10.1080/10406026.2020.1858606 .